Faktor yang berhubungan dengan status gizi balita di Kecamatan Kranggan Kabupaten Temanggung - Hariza Adnani; Indah Sovi Savitri (Jurnal Cakrawala Promkes, 2021)
Previous research found that 4.17% of children under five who experienced poor nutritional status based on body weight in Klepu Village, Krangan District, Tumangung Regency. The purpose of this study was to determine the factors related to the nutritional status of children under five in Klepu Village, Kranggan District, Temanggung Regency. This observational survey research used a cross sectional study approach. The population consisted of 72 children under five, all of them were research subjects. The data was processed using the chi square test. It was concluded that the factors related to nutritional status were infectious conditions, history of exclusive breastfeeding, history of complementary feeding and income level of parents. Meanwhile, factors that are not related to nutritional status are maternal nutritional knowledge, energy nutrition level and protein consumption level.